Očrt slovenske diplomacije ali diplomacije Slovencev - Rahten, Andrej (Teorija in praksa, 2011)
The article deals with the history of Slovenian diplomacy, which - according to the author - should not be confined to the existence of an independent Slovenian nation-state only. In addition to many prominent personalities in internal politics, Slovenians could also be found in the diplomatic services of the Habsburg Monarchy as well as the monarchic and socialist Yugoslavia. Among diplomats of Slovenian origin serving under Habsburg Emperors, the following should be mentioned: Alojz Dobravec, Chevalier de Saldapenna, Anton Lavrin, Baron Josef Schwegel, and Alojz Pogačar. During the Yugoslav Kingdom, Izidor Cankar served as an Envoy to Argentina, Canada and Greece. Between the two world wars, three Slovenians served as Envoys to Prague: Ivan Hribar, Albert Kramer and Bogumil Vošnjak. The former Prime Minister of the Provincial Government for Slovenia, Leonid Pitamic, even became an Envoy to Washington. Several Slovenians could also be found within the League of Nations. Ivan Perne was head of the League of Nations Division at the Ministry of Foreign Affairs. As for those working in the administration of the League of Nations, the highest position was taken by Vladimir Miselj, who worked in the Secretariat. After the Second World War, the leading Slovenian communist Edvard Kardelj even played - apart from Josip Broz Tito - a key role in the foreign policy of Socialist Yugoslavia. In the 1970s, the number of Slovenians in Yugoslav diplomacy began to fall, especially at the lower diplomatic levels. During the break-up of the Yugoslav state, the majority of Slovenian diplomats supported the efforts of Slovenia's political leadership to achieve independence and take an active part in struggling for international recognition.
Keywords: Diplomacija; Diplomacy; Diplomati; Diplomats; History; Zgodovina; Slovenia; Slovenija; politična zgodovina